2021
DOI: 10.1182/blood-2021-148380
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide and Rituximab (ReRi) As Front-Line Chemo-Free Therapy for Elderly Frail Patients with Diffuse Large B-Cell Lymphoma. a Phase II Study of the Fondazione Italiana Linfomi (FIL)

Abstract: INTRODUCTION Treatment of Diffuse Large B cell lymphoma (DLBCL) in the elderly population is challenging as many patients (pts) are not eligible to receive standard curative therapy, due to comorbid conditions and to a higher susceptibility to the side effects of standard anthracycline containing regimens. Among currently available active drugs, Lenalidomide has been used in the setting of relapsed/refractory DLBCL both as monotherapy and in combination with rituximab, showing a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In fact, following R-miniCHOP the 24-months disease free survival was reported to be slightly less than 60% (vs. 74% for R-DEVEC) [ 5 ]. Furthermore, two recent trials based on Rituximab-lenalidomide [ 11 ] and Rituximab-lenalidomide-ibrutinib(iR2) [ 12 ] combinations, respectively, reported a 12-months PFS of 55%, [ 11 ] and a 24-months PFS of 53%, respectively. We acknowledge these comparisons, although intriguing, remain speculative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, following R-miniCHOP the 24-months disease free survival was reported to be slightly less than 60% (vs. 74% for R-DEVEC) [ 5 ]. Furthermore, two recent trials based on Rituximab-lenalidomide [ 11 ] and Rituximab-lenalidomide-ibrutinib(iR2) [ 12 ] combinations, respectively, reported a 12-months PFS of 55%, [ 11 ] and a 24-months PFS of 53%, respectively. We acknowledge these comparisons, although intriguing, remain speculative.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, ongoing clinical trials based on immunomodulators [ 8 ], new monoclonal antibodies [ 9 ] and small molecules targeting pathogenetic pathways [ 10 ] will hopefully help a shift towards therapeutic schedules defined as chemo-free, in vulnerable DLBCL. As a matter of fact, results from a few phase II trials, based on chemo-free combinations, have already reported encouraging data [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most common G3–4 AEs were thrombocytopenia (60.2%), neutropenia (60.2%), anemia (26.9%), asthenia (19.2%), infection (15.3%), and febrile neutropenia (14.1%), with 4 (5.1%) toxic deaths (G5 febrile neutropenia with associated septic shock) as expected from the common toxicity with the use of lenalidomide schedules ( 7, 25, 26 ). Chemo-free therapies with R2 combination (rituximab–lenalidomide 20 mg D1–21) used by Wang and colleagues ( 26 ) in R/R DLBCL and by Gini and colleagues ( 25 ) in front-line DLBCL showed common G3–4 AEs, including neutropenia (52%), thrombocytopenia (36%), anemia (20%), and febrile neutropenia (11%; ref. 26 ), with 4 (5.9%) deaths (2 patients due to visceral arterial ischemia and 2 due to infectious disease; ref.…”
Section: Discussionmentioning
confidence: 99%
“… 26 ), with 4 (5.9%) deaths (2 patients due to visceral arterial ischemia and 2 due to infectious disease; ref. 25 ). R2-chemotherapy (CHOP) schedule with lenalidomide 15 mg D1–14 of every 21-day cycle, used by Nowakowski and colleagues ( 7 ) in the phase III ROBUST study with previously untreated patients with ABC-type DLBCL describes neutropenia (60%), anemia (22%), thrombocytopenia (17%), and febrile neutropenia (14%) as most common G3–4 AEs, and 3 deaths due to AEs (not otherwise specified), so lenalidomide dose adjustments were planned to manage toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Non-pegylated liposomal doxorubicin has been assessed in patients diagnosed with DLBCL, with no difference observed in cardiotoxicity [7,8]. In combination with rituximab, anthracyclinefree regimens include cyclophosphamide, vincristine and prednisone (R-COP), gemcitabine and oxaliplatin (R-GemOx), lenalidomide (R2), bendamustine, gemcitabine, cyclophosphamide, vincristine, and prednisolone (R-GCVP) [9][10][11][12]. And while these regimens are generally well tolerated showing 2-year OS ranging from 38 to 65%, these are considered palliative options.…”
Section: Dear Editormentioning
confidence: 99%